Quantitative Pitting Evaluation Stainless Steel 304 At Cooling Phase By Active Infrared Thermography With Different Target Angle - Ismon, Maznan; Syazwan Haziq Zulkurnain; Suhaimi Hassan (Research Progress in Mechanical and Manufacturing Engineering, 2020)
Infrared thermography technique used to inspect various type of problems in engineering field. In this research, active thermography method is applied to overcome the constrain to inspect the pitted location at invisible area. The main purpose of this experiment is to examine the pitted occur behind the stainless steel 304 plate and at the same time to determine the best view angle for thermography inspection. This experiment use heat gun as radiation source to transfer heat energy to the surface of stainless steel plate. The infrared camera used is FLIR T640 will be recording along the experimental process and thermal contras recorded will be analyse by using FLIR Tools software. The experiment testing will be conduct in a closed room. All of data obtain will be interpreted in graph scale by using Microsoft Excel to examine the defect area shown by temperature contras. The experiment conducted will set among 10°, 20°, 30°, 40°, 50° ,60°, 70° and 80° respectively for the view of angle. The finding of this research will determine the best angle for thermography inspection